Flipping the Tortilla: Social-Ecological Innovations and Traditional Ecological Knowledge for More Sustainable Agri-Food Systems in Spain - Guerrero Lara, Leonie; Pereira, Laura; Ravera, Federica; Jiménez Aceituno, Amanda (MDPI, 2019)
The conventional dominant global agri-food system is a main driver in the Anthropocene: food production entails profound global environmental changes from greenhouse gas emissions to biodiversity loss, and shifting diets further impact planetary and human health. Innovative approaches are needed to shift towards more sustainable, equitable and healthy agri-food systems. Building on the increasing recognition of the relevance of traditional agroecological knowledge (TAeK) in sustainable food systems, this paper aims to describe innovative agri-food initiatives and explore how the use and valorization of TAeK may transform conventional agri-food systems. It employs a case-study approach in Spain, where we conducted semi-structured interviews with 12 representatives of alternative agri-food initiatives. We found that, to promote sustainable agri-food systems, TAeK has to span from farm-to-fork. Innovative agroecological practices and knowledge help to safeguard biocultural diversity, while gastronomic knowledge among consumers on how to process and prepare local varieties and species is crucial for the implementation of shorter value chains. We discuss how TAeK enhances the success of conventional systems of innovation, challenging dominant epistemological frameworks. By scaling deep (changing values), scaling out (dissemination, reproduction) and scaling up (changing institutions), the agri-food initiatives may act on leverage points to enable broader transformation of the Spanish agri-food system.